The Combination of Platelet Rich Plasma with Skin Needling or Subcision for Postacne Scaring: a Serial Case Study - endra yustin (Stem Cell Research and Development Center, Universitas Airlangga, 2020)
Scaring in acne remains a common problem and became therapeutic challenges for the clinician. Several modalities were introduced, and combination therapies are required to achieve satisfactory results. Skin needling and subcision reported as effective methods for treating acne scar. The skin needling technique involves puncturing the skin multiple times with a small needle to induce collagen growth, while subcision worked by tunneling the connective tissue and scattered the fibrosis scar. Platelet-rich plasma (PRP) influences wound-healing by stimulating an intense inflammatory response and growth factors, these increase in the production of extracellular matrix and granulation tissue occurs, with vascular in-growth, fibroblastic proliferation, and collagen production also accelerated. Three male patients enrolled in the study, with grades 2-3 acne scar. There are three different methods of treatment were used to see the effect of the treatment. The first patient used the combination of topical PRP and skin needling, and the second patient received a combination of PRP injection and subcision, while the third patient obtains combination between topical PRP and skin needling continued with PRP injection and subcision. Our study revealed that PRP and skin needling or subcision is a simple technique and has the potential for improvement of acne scars. Three weeks after treatment, all three patient had smoother facial skin and reduction of acne scar severity. The combination of PRP and skin needling or and subcision is a simple, safe and rapid method for acne scars treatment.